TOTAL BACTERIA AND COLIFORM WASTEWATER OF TRADITIONAL CHICKEN SLAUGHTERHOUSE AFTER MORINGA SEED POWDER TREATMENT - Merdana, I Made; Suada, I Ketut; Robi, I Made; Sadhi, I Dewa Made Nurja (Buletin Veteriner Udayana, 2022)
The waste produced by the traditional chicken slaughterhouse industry consists of two types, namely solid, and liquid waste. The main solid waste consists of feathers, feces and discarded body tissue. The Liquid waste consists of washing water from chicken carcasses mixed with blood, traces of fat, and organic materials. Waste that is directly discharged into waterways without treatment has the potential to contain pathogenic microorganisms. Moringa seeds as natural coagulants contain active compounds amnosyloxy benzyl isothiocynate, tannin polyphenols, and cationic polyelectrolyte proteins. The active ingredient has antiseptic, antibacterial, and coagulation-flocculation activities. This study aims to determine the effect of Moringa seed powder concentration and sedimentation time on total bacteria and Coliform s in traditional chicken slaughterhouse wastewater. Bacterial isolation for the calculation of total bacteria using the pour plate method on the nutrient agar culture, and the total Coliform by the spread plate method on the eosin methylene blue agar culture. The results showed that the coagulation flocculation of Moringa seed powder had a significant effect (P<0.05) on the decrease in total log bacteria and Coliform wastewater of traditional chicken slaughterhouses. It can be concluded that the coagulation-flocculation of Moringa seed powder can decrease the total bacterial and Coliform with the best results at a concentration of 150 mg / L and 60 minutes deposition time.